Do virtual schools deliver in rural areas? A longitudinal analysis of academic outcomes. (July 2023) - Hamlin, Daniel; Adigun, Olajumoke; Adams, Curt
Abstract: Enrollments in full-time virtual schools have surged in recent years. One of the main arguments for virtual schools is that they extend school choice to rural areas where educational options are limited. In this study, we investigated the academic performance of virtual school students from rural areas by drawing on four years (2016–2019) of data from the US state of Oklahoma. Results show large negative associations with academic achievement for students who attend virtual schools in the overall sample ( n  = 836, 250) and for a subsample of rural students ( n  = 371, 503). Negative associations for virtual school students were also larger during elementary and middle school than in high school. This study's overall findings contribute to a growing evidence base indicating poor academic performance for virtual school students. Future research may be needed to identify conditions that foster student learning in virtual schools. Highlights: Results showed large negative associations with academic achievement for students who attended full-time virtual schools. . For virtual school students from rural areas, negative associations were similar in magnitude to those in the full sample. We found little difference in achievement based on the consistency of virtual school experiences. In virtual schools, academic performance was lower for elementary and middle school students than for high school students.